Chapter 1 An introduction to inclusive innovation - Klingler-Vidra, Robyn (Taylor & Francis, 2022)
"Innovation offers potential: to cure diseases, to better connect people, and to make the way we live and work more efficient and enjoyable. At the same time, innovation can fuel inequality, decimate livelihoods, and harm mental health. This book contends that inclusive innovation - innovation motivated by environmental and social aims - is able to uplift the benefits of innovation while reducing its harms. The book provides accessible engagement with inclusive innovation happening at the grassroots level through to policy arenas, with a focus on the South-East Asian region. Focusing on fundamental questions underpinning innovation, in terms of how, what and where, it argues that inclusive innovation has social processes and low-tech solutions as essential means of driving innovation, and that environmental concerns must be considered alongside societal aims. The book's understanding of inclusive innovation posits that marginalized or underrepresented innovators are empowered to include themselves by solving a problem that they are experiencing. The first in-depth exploration of efforts underway to assuage inequality from policy, private sector, and grassroots perspectives, this book will interest researchers in the areas of innovation studies, political economy, and development studies. "